LIKUIDITAS TINGGI, RISIKO MINIM? ANALISIS HUBUNGAN LIKUIDITAS DAN RISIKO KEUANGAN PERUSAHAAN MANUFAKTUR DI INDONESIA - Wulandari, Ayu; Sari, Vila Novita (PT Naureen Digital Education, 2025)
This study aims to analyze the effect of liquidity on financial risk in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The research method used is quantitative causality. The data source in this study uses secondary data in the form of annual financial reports of manufacturing companies in Indonesia. The research sample technique used a purposive sampling technique with certain criteria, resulting in 30 manufacturing companies as research samples. The results of the analysis show that liquidity, as measured by the cash ratio, has a significant influence on the debt to asset ratio in manufacturing companies. This finding indicates that optimal liquidity management can reduce the company's financial risk. The implication of this study is the need for manufacturing companies to pay attention to liquidity management in order to improve financial stability, especially in the face of unstable economic conditions